Environmental innovation and financial performance: A case study of mediating role of environmental management - Yuniarti, Evi; Nurmala, Nurmala; Asliana, Endang; Mursalin, M; Satpathy, Maheswar; Attiya, Adel A.; Secelean, Nicolae Adrian (Electronic Journal of Education, Social Economics and Technology, 2023)
The purpose of this study is to investigate the impact of environmental innovation which is product innovation (PDI) and process innovation (PCI) on firm’s financial performance (FFP). And also, to investigate mediating role of the environment management accounting (EMA) against innovation and FFP. Data were collected from 98 respondents, worked in management positions in Indonesia’s manufacturing sectors. The study uses PLS-SEM (partial least square based structural equation modeling) software for the data analysis. The results showed that PDI has positive and significant impacts on FFP. But PCI has not significant impacts on FFP. Furthermore, PDI and PCI have significant impacts on EMA. This study also indicated that EMA mediate the relationship between innovation and FFP in the manufacturing sector of Indonesia. This study suggests the managers of the manufacturing companies or similar sectors to introduce innovations in their products and processes for developing a better EMA system.  The current study also tends to assist policymakers in developing appropriate policies for the manufacturing sector of Indonesia by realizing the importance of environmental innovation, EMA, so that their environmental and economic impacts can be managed and regulated.